The bright and dark side of humble leadership for project success: A conservation of resources perspective - Saad Hassan; Hira Nasim; Muzammel Shah; Amir Ishaque; Mahin Fiza (Cogent Business & Management, 2023)
Drawing on conservation of resources theory, this study explores the bright and dark side of humble leadership by examining the mediating role of project commitment and workplace deviance between humble leadership and project success. Data were collected from 315 IT employees followed by partial least square structure equation modeling (PLS-SEM) to test the hypotheses. Findings indicate that humble leadership positively effects project success through the mediation of project commitment. However, workplace deviance does not mediate the link between humble leadership and project success. Study contributes to the nascent literature by highlighting humble leadership as an effective leadership style for project success.
Keywords: 650; humble leadership; project commitment; project success; workplace deviance